2017
DOI: 10.18632/oncotarget.18868
|View full text |Cite
|
Sign up to set email alerts
|

DEPDC1 is required for cell cycle progression and motility in nasopharyngeal carcinoma

Abstract: DEP domain containing 1 (DEPDC1) is a newly identified cancer-related and cell cycle related gene and has been demonstrated as a novel therapeutic target for bladder cancer. However, the functional involvement and therapeutic potential of DEPDC1 in nasopharyngeal carcinoma (NPC) remains unclear. Our results showed that DEPDC1 was overexpressed at both mRNA and protein levels in NPC tissues compared with normal or non-tumor tissues. The siRNA-mediated DEPDC1 depletion resulted in significant inhibition of proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…Among the proliferation-associated genes downregulated after SOX6 knockdown ( Fig. 3b), three genes (CDCA3, DEPDC1 and E2F8) appeared as plausible candidate genes to promote the pro-proliferative phenotype of SOX6, as they were previously shown to be involved in cell cycle progression [29][30][31][32] . In accordance, knockdown of any one of the genes with specific sipools in RDES and TC-32 EwS cells phenocopied, at least in part, the proliferative effect of SOX6 ( Supplementary Fig.…”
Section: Sox6-silenced Cells (Supplementarymentioning
confidence: 77%
“…Among the proliferation-associated genes downregulated after SOX6 knockdown ( Fig. 3b), three genes (CDCA3, DEPDC1 and E2F8) appeared as plausible candidate genes to promote the pro-proliferative phenotype of SOX6, as they were previously shown to be involved in cell cycle progression [29][30][31][32] . In accordance, knockdown of any one of the genes with specific sipools in RDES and TC-32 EwS cells phenocopied, at least in part, the proliferative effect of SOX6 ( Supplementary Fig.…”
Section: Sox6-silenced Cells (Supplementarymentioning
confidence: 77%
“…Previous studies have indicated that DEPDC1 is elevated in several types of cancer and is implicated in tumorigenesis (6)(7)(8)(9)(10). It has also been revealed that DEPDC1 is upregulated in HCC tissue and may therefore be an independent predictor of HCC (11).…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily expressed in the testis and is not detected in other normal human tissues (6). Recently, several studies revealed that DEPDC1 was upregulated in many tumor types, indicating its important role in tumorigenesis (7)(8)(9)(10). For example, DEPDC1 was upregulated in bladder carcinogenesis and the inhibition of DEPDC1 via small-interfering RNA (siRNA) significantly suppressed the growth of bladder cancer cells (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that DEPDC1 is aberrantly overexpressed in diverse human cancers and acts as an oncogene in tumorigenesis and tumor progression. [23][24][25][26] In a previous study, Feng et al 27 reported that DEPDC1 is essentially required for accelerating cell cycle progression and motility in nasopharyngeal carcinoma through the NF-κB signal pathway. In another study, researchers discovered an oncogenic role of DEPDC1 in prostate cancer through activation of E2F signaling which has a broad impact on HCC progression.…”
Section: Discussionmentioning
confidence: 99%